Maximal buttonings of non-tree graphs - Wanchai Tapanyo (2018)
© 2017 by the Mathematical Association of Thailand. All rights reserved. Let G be a finite connected graph of n vertices v 1 , v 2 ,…, v n . A buttoning of G is a closed walk consisting of n shortest paths [v 1 , v 2 ], [v 2 , v 3 ],…, [v n−1 , v n ], [v n , v 1 ]. The buttoning is said to be maximal if it has a maximum length when compared with all other buttonings of G. The goal of this work is to find a length of a maximal buttoning of non-tree graphs: complete multipartite graphs, grid graphs and rooted products of graphs.